Pembelajaran Calistung: Peningkatkan Perkembangan Kognitif pada Kelompok B di TK Angkasa Tasikmalaya - Asrilla Yulisar, Niffa; Hibana, Hibana; Zubaedah, Siti (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
This research is motivated by the pros and cons of applying calistung learning in kindergarten. Calistung's activities caused much criticism from observers of early childhood. That the world of children is playing and having fun and the most important thing that must be developed in kindergarten is socializing and ethics. But there are opinions that assume that early childhood is a golden period where it is easy to absorb all kinds of information. This study includes a qualitative approach to the type of descriptive research. The subject of this research is the teacher kelas B TK Angkasa Tasikmalaya. Data collection uses observation, interviews and documentation. Analysis using the Milles and Huberman model and data validity testing using source and technique triangulation. The results showed that the learning that was implemented in TK Angkasa had largely followed the idealism of calistung learning according to existing theories. Children's cognitive aspects generally develop well according to the stages of cognitive development at the age of 5-6 years. Calistung learning in TK Angkasa Tasikmalaya has positive and negative effects on children's cognitive.